INVESTIGATING LIGNIN-MODIFYING ENZYMES FOR SUSTAINABLE PULP AND PAPER PRODUCTION - Buhari, F.; Njoku, K. L.; Oboh, B.; Owolabi, F. A. T. (FUDMA JOURNAL OF SCIENCES, 2025)
The pulp and paper industry is under pressure to reduce its reliance on conventional pulping methods that involve harsh chemicals, high energy input and the generation of toxic effluents. This study presents a sustainable alternative using enzyme-assisted alkaline peroxide pretreatment for pulping agricultural residues, specifically corn (Zea mays) husk and pineapple (Ananas comosus) crown. Xylanase and ligninase enzymes produced from Aspergillus niger and Trichoderma reesei grown on agro-waste substrates, were evaluated for their delignification potential. Enzyme activity was measured using UV spectrophotometry while lignin removal post-treatment was quantified chemically. Among the enzymes tested, xylanase demonstrated the highest delignification efficiency. Peak xylanase activity on pineapple crown was recorded at 3.4854 nm after 96 hours, while corn husk showed a maximum activity of 1.9535 nm at 72 hours. These variations underscore the importance of enzyme-substrate compatibility and incubation time for optimal performance. Xylanase pretreatment led to substantial lignin reductions of 64.91% for pineapple crown and 60.61% for corn husk facilitating improved fiber liberation. This enhances pulp yield, fiber bonding, and paper strength making the process suitable for industrial application. By integrating enzymatic treatment with alkaline peroxide pretreatment, this method offers an eco-friendly pulping approach that reduces chemical dependency and environmental burden. Furthermore, the use of agricultural residues promotes waste valorization and supports a circular bioeconomy. This research demonstrates the viability of enzyme-assisted pulping as a green technology pathway, advancing both environmental sustainability and economic efficiency in the pulp and paper industry.